Related factors for worsening renal function following percutaneous transluminal renal angioplasty (PTRA) in patients with atherosclerotic renal artery stenosis. (3rd October 2015) - Yoshihara, Fumiki; Fukuda, Tetsuya; Iwashima, Yoshio; Nakamura, Satoko; Hayashi, Shin-Ichiro; Kishida, Masatsugu; Ishizuka, Azusa; Kusunoki, Hiroshi; Ohta, Yuko; Kawano, Yuhei
Abstract: Purpose : To identify candidates for PTRA in terms of the preservation of renal function, we herein evaluated factors that caused worsening renal function (WRF) after PTRA. Methods : We evaluated 92 patients with atherosclerotic renal artery stenosis (mean age 70.7 ± 8.4 years). WRF was defined as a ≥0.3 mg/dL increase in creatinine levels after PTRA compared to before PTRA. Results : A total of 92 patients exhibited non-WRF 83 (90.2%), WRF 9 (9.8%). Significant differences were observed in serum creatinine levels between two groups both before (non-WRF 1.34 ± 0.49 versus WRF 1.70 ± 0.68 mg/dL, p =  0.0462) and after PTRA (non-WRF 1.31 ± 0.43 versus WRF 2.42 ± 1.12 mg/dL, p  < 0.0001). Patients with WRF had higher comorbidity rate of diabetes mellitus (DM) (non-WRF 31.3% versus WRF 66.7%, p =  0.0345) and proteinuria (non-WRF 27.7% versus WRF 66.7%, p =  0.0169), and had higher systolic blood pressure (non-WRF 143.6 ± 18.7 versus WRF 157.1 ± 19.9 mmHg, p =  0.0436), higher plasma B-type natriuretic peptide (BNP) levels, and larger left atrial and left ventricular end-diastolic dimensions before PTRA. Patients with WRF had a higher rate of taking diuretics (non-WRF 27.7% versus WRF 66.7%, p =  0.0169) after PTRA. Multiple logistic regression analysis revealed that comorbidity of DM was an independent related factor for WRF (comorbidity of DM, yes: OR 31.0, 95% CI 2.44–1024.62, p =  0.0055). Conclusions : Comorbidity of DM, coexisting of proteinuria, high creatinine level, high blood pressure, high BNP levels, and large left atrial and ventricular dimensions were related to WRF after PTRA in patients with atherosclerotic renal artery stenosis.